'Thermo cup' / Ariff Muhammad Mat Saad...[et al.] - Mat Saad, Ariff Muhammad; Abdul Talib, Muhammad Akhmal; Mohd Hilmi Raja, Syahnur Fitri; R.Azmi, Muhammad Hazziq (2017)
Nowadays, there are full of technological appliances. As the time progress, more gadgets and gizmos are developing either a prototype or a kick start. As entrepreneur, one must develop a new and innovative product that can give benefit to society. Furthermore, the product also must be able to capture people's attention. The product must be able to solve people's problems and make our daily life easier. Thus, we have a perfect, simple solution yet beneficial to everyone's daily life. The working environments are so busy. Many people becoming stress due to works they must complete in order to keep surviving. Therefore, they need something that can improve their mood in order to ease their mind. One of the easiest ways to reduce our stress is by drinking a cup of hot coffee. However, without noticing, the coffee got cold faster and cannot maintain its temperature. Or in other hand, during hot sunny day people want to relax their body by drinking cold water. But, the water cannot maintain its coldness in a long period of time. People can't put their drink in freezer if they go out from their house. So, in order to overcome this problem, we have invented a product to ensure people can fully enjoy their lives. The Thermo Cup is an innovative product that able to help people drink their drinks at their desirable temperature. At people's desire and will, their stress will reduce and ultimately will be more productive and efficient at doing their work. With research and resources pulled, we are able to invent a working, tested and innovative creation that helps people reduces stress, conduct their work efficiently, and maintaining happy attitude by a cup of drink.